Chapter "We are all Demoiselles d'Avignon" or the Breaching of the Dominant Gaze - Méndez Baiges, Maite (Studi e saggi, 2022)
In his thesis on Les Demoiselles d'Avignon, Steinberg postulated the fundamental role of the spectator (object of the appealing gazes of the five young nudes in the painting) as the catalyst of the meanings in the painting. From then on new critical perspectives would speculate about this subject, targeted by the personages in the painting, who bears so much responsibility in articulating the interpretation of the scene. Doubts were raised about the universal character of the gaze, the universal character of the receptor of the work of art and of Modern Art. From the end of the 20th century and activated by the most recent methodological approaches such as feminism and post-colonialism, new critical voices provoked the breaching of the dominating gaze. This chapter broaches the interpretations of this paradigmatic work of Modern Art made by feminist and post-colonial and subaltern theories, questioning the very proposals of Modernism. Feminism shows how gender conditioning affects the reception of a work of art. And allied with this, post-colonialism and subaltern theory begin to seriously question the way historiography has considered, or not, the relevance of Art négre in the avant-guard eclosion.